Literature Review of Library Information System Audit Using COBIT 5 Framework - Annisa Khairani; Dini Rahma Aliyah; Mudtiani Hakim Br Bangun; Yulia Ribuna Br Bangun; Meigia Nidya Sari (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to analyze and determine the effect of e government on the quality of public services in Indonesia. This e government also uses a modern strategy that utilizes information and communication technology (ICT) to improve efficiency, transparency, and accessibility of public services. With a qualitative descriptive method, E government has a positive impact on the effectiveness of public services, such as increasing public satisfaction, service responsiveness, and operational efficiency. Implementation challenges include limited infrastructure, low digital literacy, organizational culture resistance, and budget constraints. The results of this study include improving ICT infrastructure, human resource training, intensifying socialization to the community, and developing policies that support digital transformation.